Menegosiasikan Harmoni Melalui Kuliner: Simbolisme Lontong Cap Go Meh dalam Perayaan Grebeg Sudiro di Surakarta - Nabillah Mahdiana; Warto Warto; Hieronymus Purwanta (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Grebeg Sudiro celebration in Surakarta represents a harmonious coexistence between the Javanese and Chinese communities, born of a post-conflict collective consciousness. This study aims to uncover the symbolic meaning and cultural negotiation process through the Lontong Cap Go Meh culinary dish as a means of fostering intercultural harmony. This study uses a qualitative method with a cultural approach to analyze various cross-disciplinary literature data through the framework of Ernest E. Boesch's Symbolic Action Theory. The results show that Lontong Cap Go Meh is not simply a consumer product, but rather a symbolic act that represents acculturation through the adaptation of local ingredients, cooking techniques, and an inclusive presentation philosophy. This culinary dish functions as a medium of negotiation that dissolves ethnic boundaries and becomes a non-verbal communication language to rebuild the image of the Chinese community in public spaces. The conclusion of the study confirms that Lontong Cap Go Meh serves as a symbol of openness that actively communicates messages of harmony and social integration for a more stable future for a multicultural society in Surakarta.